2016
DOI: 10.18805/lr.v0iof.10284
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing resistance of rice bean to diseases by seed treatment with Pseudomonas flourescens and Bacillus species

Abstract: Efficacy of seed bacterization with six rhizobacterial isolates was assessed in laboratory conditions to evaluate their resistance inducing ability in rice bean. Pseudomonas. fluorescens isolates B 5 , B 6 , B 8 , B 9 and B 17 and Bacillus species isolate B 18 were found effective in reducing the percentage of diseased seedling but showed the plant growth promotion. Increased levels of catalase, phenylalanine ammonia lyase (PAL) and poly phenol oxidase (PPO) were observed in seedlings indicating higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In vitro study revealed significant (63%) inhibition of mycelial growth of the R. solani by the test bacterium compared to untreated control (Fig 1). Accordingly, several previous studies have reported the activity of Bacillus amyloliquefaciens against various fungal phytopathogens like Fusarium asiaticum, Fusarium graminearum, Rhizoctonia solani and Botrytis cinerea (Gupta et al, 2016;Boottanun et al, 2017;Ntushelo et al, 2019). The suppression of Rhizoctonia sp.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro study revealed significant (63%) inhibition of mycelial growth of the R. solani by the test bacterium compared to untreated control (Fig 1). Accordingly, several previous studies have reported the activity of Bacillus amyloliquefaciens against various fungal phytopathogens like Fusarium asiaticum, Fusarium graminearum, Rhizoctonia solani and Botrytis cinerea (Gupta et al, 2016;Boottanun et al, 2017;Ntushelo et al, 2019). The suppression of Rhizoctonia sp.…”
Section: Resultsmentioning
confidence: 99%
“…Various species of B. subtilis have been reported as PGPR. According to Gupta et al (2016), Bacillus spiece isolate B18 were found effective as PGPR. The PGPR improve plant physiological state by phytohormones production or by releasing beneficial organic compounds (Kumar and Kumar, 2012).…”
Section: Plant Growth Promotionmentioning
confidence: 99%
“…In this regard, Bacillus species have been used to control plant diseases as biological control agents (Gupta et al, 2016;Jangir et al, 2018;Le et al, 2019;Sunkad et al, 2023). Bacillus is known to produce a wide range of biocompounds such as bacteriocins and lipopeptides that inhibit fungal growth and limit the diseases (Pradhan et al, 2018;Rodríguez et al, 2018;Le et al, 2018Le et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%